Identifying and targeting the initial adopters for optimal social contagion - Zhang, Zhiyuan (2017)
In this report we aim to study the society interactions among human. In more precise terms, the report studies the social contagions in a complex network. From past studies, there was a deficiency in the investigations on the influence of susceptible individuals1 and the susceptibility of influence individuals2. Previous studies have also proposed the assumption that societal diffusion is steered by susceptibility of the society; as opposed to what many believe to be the notion that the influential individuals play the pivotal role in social dissemination. However few studies have been done to justify this inclination, leaving scarce proofs to substantiate this claim. This study serves to address the above-mentioned gaps in the research of social contagion in a network and propose plausible justifications for the outcomes. The result shows that in a complex network, susceptible individuals exhibit a lower influence whereas influential individuals reveal a lower susceptibility towards external influence. The study also affirms the speculation that social circulation is actuated by the susceptibility of the society. Lastly, the results from the simulations also showed that when there are a large proportion of susceptible agents in the society, social diffusion would be more effective when the normal individuals having the most number of susceptible friends are being activated as the initial adopters3.